Technological Innovation for Population Administration: Web-Based System in Cisontrol Village, Ciamis - Ajeng Mayang; Yudi Barnadi; Ase Suryana; Neris Peri Ardiansyah (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
The rapid development of information technology has profoundly influenced various sectors, including government operations and economic frameworks. This research specifically examines Cisontrol Village in Ciamis, West Java, which encounters numerous challenges in promoting its regional potential and efficiently managing population administration. The inefficiencies in the administration of population data and business permits have particularly hindered the growth of Micro, Small, and Medium Enterprises (MSMEs) within the village. To tackle these challenges, this research proposes a comprehensive web-based population administration information system designed to streamline the application process for the Business Permit for Trade (SIUP) specifically for MSME operators. The implementation of this system is aimed at enhancing the efficiency and accuracy of administrative tasks, allowing residents easy access to the information they need. By providing a user-friendly platform, local entrepreneurs can navigate the complexities of the permitting process with greater ease, thereby reducing the bureaucratic burden often associated with starting and running a business. Preliminary results indicate that good archiving practices within the system will support the delivery of precise and accurate information, ultimately improving the quality of administrative services in Cisontrol Village. This enhancement is expected to expedite various administrative processes, which will not only save time for residents but will also contribute to a more favorable business environment. Furthermore, by facilitating local economic development through better administrative practices, the web-based system encourages entrepreneurship and supports the establishment of new businesses. In conclusion, the introduction of this innovative information system holds the potential to significantly improve administrative efficiency and promote sustainable economic growth, positively impacting the overall quality of life for the residents of Cisontrol Village.